Driving forces for the adsorption of a His-tag Chagas antigen: a rational approach to design bio-functional surfaces - Valenti, Laura Elisa (2013)
In order to rationally design a bio-functional surface based on the adsorption of a His-tag antigen, three requirements have to be considered: the bio-recognition element, the driving forces for the adsorption process and the detection mode of the bio-recognition event. This work is focused on the study of the adsorption mechanism of the His-tag H49 Chagas antigen on Ni(II) modified substrates. In order to construct the bio-functional surface, the gen of the H49 Chagas antigen was modified to incorporate His6 moiety at the N-terminal (His6-H49). Then, its physical adsorption and bio-affinity interaction with the solid substrate was studied by reflectometry. Besides His-Ni(II) bio-affinity interactions, His6-H49 was also physically adsorbed on Ni(II) modified substrates, leading to randomly oriented antigens. These loosely attached bio-molecules were partially removed using conditions of electrostatic repulsion. On the other hand, bio-affinity interactions, resulting in site-oriented molecules on the substrate, were only removable by specific competitors for Ni(II) surface sites. Finally, the surface bio-activity was determined from the peak separations of voltammetry waves due to the change of the electron transfer kinetics of a redox probe through the bio-functional surface (working electrode).